Avaliacao Isocinetica em Jogadoresde Futebol Profissional e Comparaçao do Desempenho Entre as Diferentes Posicoes Ocupadas no Campo - Weber, F. S.; Silva, B. G. C. da; Radaelli, R.; Paiva, C.; Pinto, R. S. (Revista Brasileira de Medicina do Esporte, 2010)
The aim of this study was to analyze the data collected from the peak torque (PT) and the fatigue index in isokinetic tests from forwards (F), midfielders (M) and defenders (D) in order to draw a profile of these athletes. Twenty-seven elite male soccer players (mean age 26.55± 5.1 years) were tested, and divided in groups F (6), M (7) and D (14). They were submitted to an isokinetic test with five maximal repetitions of knee flexion (concentric and eccentric) and extension (concentric) at 60°/s and 30 maximal concentric repetitions (flexion and extension) at 300°/s. The collected data evidenced that group D showed significantly higher values of concentric flexors PT at 60 °/s on the dominant side (DS) compared to M (p = 0.05). However, for the other PT variables and fatigue index no differences were found between positions. Concerning bilateral deficit (BD), the athletes presented values within normality. Regarding ratios, it was observed that the players were within the normative values for conventional ratio, but were below the normal values for the functional ratio. We concluded that despite the different positions in the field the players have, this fact does not seem to dramatically influence on the majority of neuromuscular characteristics of lower limbs in the assessed soccer players.